1983
DOI: 10.1111/j.1476-5381.1983.tb11020.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses in rats with glycerol‐induced acute renal failure

Abstract: The present findings show that in the rat, changes in cardiovascular responsiveness occur after a brief period of uraemia which are similar to those observed in patients and rats with chronic renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
6
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
7
6
0
Order By: Relevance
“…The decreased vascular reactivity to noradrenaline supports our previous findings of reduced pressor responses to noradrenaline in uraemic rats (Bowmer et al, 1983). Similarly diminished vascular responses to noradrenaline have been observed both in humans and rats with chronic renal failure (Campese et al, 1981;Rascher etal., 1982) and in rats with ARF produced by bilateral ureter ligation (Ueda etal., 1981).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The decreased vascular reactivity to noradrenaline supports our previous findings of reduced pressor responses to noradrenaline in uraemic rats (Bowmer et al, 1983). Similarly diminished vascular responses to noradrenaline have been observed both in humans and rats with chronic renal failure (Campese et al, 1981;Rascher etal., 1982) and in rats with ARF produced by bilateral ureter ligation (Ueda etal., 1981).…”
Section: Discussionsupporting
confidence: 79%
“…They concluded that the decreased response to noradrenaline in renal failure was due to downregulation of a-receptors in response to elevated circulating noradrenaline levels. Whilst we too have found increased plasma noradrenaline concentrations in glycerol-induced ARF (Bowmer et al, 1983) the decreased vascular responses to noradrenaline, angiotensin and potassium chloride observed in the present study suggest that, at least in this acute model of renal failure, the depression of vascular responses is less specific and not restricted to noradrenaline. The decreased contractions of the isolated blood vessels from uraemic animals to angiotensin (Figure 2) is paralleled by the reduced pressor responses to the peptide in vivo (Figure 4) which supports similar findings observed in the investigation of ARF produced by ureter ligation (Ueda etal., 1981).…”
Section: Discussionmentioning
confidence: 37%
See 1 more Smart Citation
“…[15] performed in the model of glycerol induced AKI. These authors considered high uremia (plasma urea was signifi cantly elevated in the AKI group in our study as well) and its infl uence on the autonomic nervous system (diminished α 1 adrenoreceptors sensitivity) as a cause of MAP reduction after AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of rats with acute renal failure (ARF) have demonstrated abnormalities in the sympathetic influence on cardiac function. For example, depressed chronotropic responses in-vivo to cervical sympathetic stimulation and isoprenaline have been noted (Bowmer et al 1983;Yates et a1 1985Yates et a1 , 1986Mann et al 1986) and isolated right atria from rats with A R F exhibit reduced chronotropic responses to isoprenaline (Yates et al 1985). In addition to an impairment in cardiac chronotropic responses, we have observed that right ventricular strips removed from rats with A R F display reduced inotropic responses to a variety of cardiac stimulants, including isoprenaline, 3-isobutyl-I-methylxanthine and Ca2+.…”
mentioning
confidence: 99%